2014
DOI: 10.1111/aji.12268
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Therapy Differently Regulates the Anti‐ and Pro‐Inflammatory Cytokines in the Plasma and Prostate of Rats Submitted to Chronic Ethanol Consumption (UChB)

Abstract: So, ethanol and testosterone differentially modulates the cytokines in the plasma and prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…These previous animal studies as well as the current one indicated that exogenous testosterone supplementation might not alter the cytokines production in the body. On the other hand, Mendes et al showed that the combination of ethanol consumption and testosterone treatment (testosterone cypionate 5 mg/kg every other day for 4 weeks) caused a significant increase in TNFα, but not IL-6 in rats ( 15 ). However, each compound alone did not significantly change the level of cytokines in rats ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These previous animal studies as well as the current one indicated that exogenous testosterone supplementation might not alter the cytokines production in the body. On the other hand, Mendes et al showed that the combination of ethanol consumption and testosterone treatment (testosterone cypionate 5 mg/kg every other day for 4 weeks) caused a significant increase in TNFα, but not IL-6 in rats ( 15 ). However, each compound alone did not significantly change the level of cytokines in rats ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Mendes et al showed that the combination of ethanol consumption and testosterone treatment (testosterone cypionate 5 mg/kg every other day for 4 weeks) caused a significant increase in TNFα, but not IL-6 in rats ( 15 ). However, each compound alone did not significantly change the level of cytokines in rats ( 15 ). The results of the study by Mendes et al pointed out that exogenous testosterone supplementation might aggravate the inflammatory properties of other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large amount of data regarding prostatic changes caused by ethanol (Fioruci‐Fontanelli et al, 2015), the mechanisms by which chronic alcohol consumption modulates metabolism in the prostate remain poorly understood. The earliest studies about effects of alcohol consumption in the prostate suggested that long‐term drinking is associated with inflammation (Mendes et al, 2014), decreases in levels of retinoic acid via CYP2E1 enzyme is involved mainly in the catabolism of ethanol (Fioruci‐Fontanelli et al, 2015), increased lipids accumulation in cytoplasmatic cell (You & Arteel, 2019), increased serum estrogen resulting in hyperproliferation related with prostatic intraepithelial neoplasia (PIN). In addition, results show genotoxic effects of acetaldehyde, a product of the oxidation of ethanol, induces the activation of microsomal cytochrome P450 2E1 (CYP2E1), a process that produces reactive oxygen species, that leads to lipid peroxidation and mutagenic adducts (Deshpande et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The minimum detection limits were 21 pg/mL (IL‐6), 10 pg/mL (IL‐10), 5 pg/mL (TNF‐α), and 4.6 pg/mL (TGF‐β1). The protocol was standardized according to Mendes et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The number of intact and degranulated mast cells was measured in five animals of each experimental group and the values were given in cell/mm 2 . Random images of 50 histological fields per experimental group (10 fields/rat as described in morphometric–stereological analysis) of were captured by digital photomicroscope Axiophot II—Zeiss using 40× objective, with each field covering an area of 0.085 mm 2 , according to Mendes et al ().…”
Section: Methodsmentioning
confidence: 99%